PENGARUH MOTIVASI, FEE AUDIT DAN PENGALAMAN AUDITOR TERHADAP PELAKSANAAN AUDIT PADA UMKM - Kristianto, Giovanny Bangun; Dianningsih, Dianningsih (Universitas Muhammadiyah Tangerang, 2024)
The rapid growth of MSMEs in Indonesia has affected the economy in Indonesia. This economic equality receives support from the government with ease in capital matters. Achieving this capital requires a financial report that must be prepared by MSME activists, and to further improve the economy, the financial report must go through a review or audit process by a public accounting firm. In this research, there are three variables that influence the implementation of MSME audits, namely the motivation of an auditor, the audit fee given for audit services and audit experience. This research aims to determine whether motivation, audit fees and auditor experience have an influence on the implementation of MSME audits, both simultaneously and partially. Data analysis in this study used SPSS with multiple linear regression. The test results show that both partially and simultaneously the three variables, namely auditor motivation, audit fees and audit experience have a significant and positive influence on the implementation of audits in MSMEs.